Design of Soybean Dregs Separator Tool for Tempe Production in MSMEs Pasuruan Regency Using Pulse Method and Rula Method - Ayik Pusaka Ningwati; Achmad Misbah; Muhammad Hermansyah (Journal Knowledge Industrial Engineering (JKIE), 2022)
Micro, Small and Medium Enterprises (MSMEs) are a source of the regional and national economy. MSMEs have many roles in the social economy including being the main actor in economic activity, providing employment, playing a role in local economic development and community empowerment, a source of innovation, and creating new markets. Pasuruan Regency is one of the tempe centers in East Java. More than 200 families are engaged in Tempe production, including those in the Bangil sub-district, Purwodadi sub-district, Kejayan sub-district and Sukorejo sub-district. The main problem faced by Tempe Production SMEs is the machine or soybean dregs separator used, still using traditional tools (humans) which are less effective and efficient so that it takes a long time and there are working positions for workers who lack ergonomics, causing workload which is more. The purpose of this activity is how to make or design a design tool and work aid test for soybean dregs separator machines from soybean seeds to reduce the workload of making soybeans into tempeh and to be able to reduce the portion of the workload on tempe-making workers with anthropometric calculations.